Experimental Study on Mixed Combustion Characteristics of Methanol/Diesel Pool Fires in Engine Rooms of Hybrid Ships - Jiaqi Dong; Zhongzheng Wu; Jinqi Han; Jianghao Li; Jiacheng Liu; Yunfeng Yan; Liang Wang (Energies)
Methanol/diesel hybrid−powered vessels represent a significant advancement in green and low−carbon innovation in the maritime transportation sector and have been widely adopted across various shipping markets. However, the dual−fuel power system modifies the fire load within the engine room compared to traditional vessels, thereby significantly influencing the fire safety of methanol/diesel−powered ships. In this study, anhydrous methanol and light−duty diesel (with 0 °C pour point) were used as fuels to investigate the mixed combustion characteristics of these immiscible fuels in circular pools with diameters of 6, 10, 14, and 20 cm at various mixing ratios. By analyzing the fuel mass loss rate, flame morphology, and heat transfer characteristics, it was determined that methanol and diesel exhibited distinct stratification during combustion, with the process comprising three phases: pure methanol combustion phase, transitional combustion phase, and pure diesel combustion phase. Slopover occurred during the transitional combustion phase, and its intensity decreased as the pool diameter or methanol fuel quantity increased. Based on this conclusion, a quantitative relationship was established between slopover intensity, pool diameter, and the methanol/diesel volume ratio. Additionally, during the transitional combustion phase, the average flame height exhibited an exponential coupling relationship with the pool diameter and the methanol/diesel volume ratio. Therefore, a modification was made to the classical flame height model to account for these effects. Moreover, a prediction model for the burning rate of methanol/diesel pool fires was established based on transient temperature variations within the fuel layer. This model incorporated a correction factor related to pool diameter and fuel mixture ratio. Additionally, the causes of slopover were analyzed from the perspectives of heat transfer and fire dynamics, further refining the physical interpretation of the correction factor.